Violencia familiar - CADOCHE, Sara Noemí dir. (RUBINZAL-CULZONI, 2002)
Autores:AZVALINSKY, Alejandro M.; BRINGIOTTI, María Inés; CHIAVARINI, Ana María; CORSI, Jorge; FAINBLUM, Alicia; FERREIRA, Graciela B.; GOMEZ, Julio Luis; GROSMAN, CECILIA P.; IÑIGO, Delia B.; LIPONEZKY DE AMAVET, Sara; LLOVERAS, Nora; MANZI DE GARCIA PUENTE, Lura; MOLINA, Adriana; NANI, Ester; ORTENBERG, Osvaldo D.; RIVERO, María Rosa; SUAREZ, Teresa